2022
DOI: 10.3390/life12081108
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MDA5 Amyopathic Dermatomyositis—A Diagnostic and Therapeutic Challenge

Abstract: Clinically amyopathic Dermatomyositis (CADM) is a rare subtype of idiopathic inflammatory myositis, associated with no muscular manifestations, which is more frequent in Asian women. Anti-melanoma differentiation-associated gene 5 (MDA5) antibodies are a recently discovered type of specific autoantibodies associated with myositis. The anti-MDA5 DM was initially described in Japan and later it was discovered that the target antigen was a protein implicated in the innate immune response against viruses, that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Several COVID-19 era case reports or series of MDA5+ myositis or ILD have been reported in the UK and internationally either in the setting of infection or post-vaccination. 2 , 3 , 4 , 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 Our study is the largest one to document the features and outcomes of this clinical syndrome, especially in 2021. Approximately 42% of our MDA5+ cases have thus far have progressive ILD, with a third of these proving fatal so far, in keeping with the known aggressive course of MDA5 + -ILD.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several COVID-19 era case reports or series of MDA5+ myositis or ILD have been reported in the UK and internationally either in the setting of infection or post-vaccination. 2 , 3 , 4 , 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 Our study is the largest one to document the features and outcomes of this clinical syndrome, especially in 2021. Approximately 42% of our MDA5+ cases have thus far have progressive ILD, with a third of these proving fatal so far, in keeping with the known aggressive course of MDA5 + -ILD.…”
Section: Discussionmentioning
confidence: 94%
“…This was based on both increased rate of anti-MDA5 related immunology reporting and multiple physicians seeing MDA5 related disease for the first time, combined with emergent literature reporting COVID-19 era anti-MDA5-related disease. 2 , 3 , 4 , 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 We collected data on the number of MDA5+ tests per year between January 2018 and December 2022. The clinical notes review focused on patterns of symptomatic MDA5 disease (including degree of ILD); muscle or other organs involvement, therapy, therapy responses and survival data.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to our results, Mamyrova et al 9 reported a more frequent rate of anti‐p155/140 (TIF‐1) ab positivity in CAJDM patients. Anti‐MDA‐5 exhibits a relationship with amyopathic dermatomyositis in adults 19 . However, such a relationship was not observed in children with CAJDM 9 .…”
Section: Discussionmentioning
confidence: 96%
“…Anti-MDA-5 exhibits a relationship with amyopathic dermatomyositis in adults. 19 However, such a relationship was not observed in children with CAJDM. 9 In our cohort, only 1 patient with CAJDM had anti-MDA-5 ab positivity.…”
Section: Discussionmentioning
confidence: 98%
“…We audited the increased anti-MDA5 positivity in relationship to other MSA (Euroimmun immunoblot©) that included MDA5 + cases. This was based on both increased rate of anti-MDA5 related immunology reporting and multiple physicians seeing MDA5 related disease for the first time, combined with emergent literature reporting COVID-19 era anti-MDA5-related disease [1][2][3][4][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . We collected data on the number of MDA5+ tests per year between January 2018 to December 2022.…”
Section: Methodsmentioning
confidence: 99%